Frequência alélica de sete marcadores Short Tandem Repeat em indivíduos do estado do Rio Grande do Sul, Brasil - Gastaldo, André Zoratto (2012)
Population data of seven short tandem repeat loci of the PowerPlex® CS7 were obtained from a sample of 401 individuals from Rio Grande do Sul (Southern Brazil). The loci are the two pentanucleotides STRs in the PowerPlex® 16 (PENTA D and PENTA E), an extra pentanucleotide (PENTA C), and four loci STR in the FFFL Fluorescent STR System (LPL, F13B, FES/FPS, and F13A01). Allele frequency and other forensically relevant statistics data were generated for these seven loci. All of the analyzed loci meet Hardy-Weinberg equilibrium expectations and no linkage disequilibrium were found, except for LPL locus. The observed and expected heterozygosity, power of discrimination and exclusion and polymorphic information content were calculated. The combined power of discrimination and combined power of exclusion were 0.999999987 and 0.998159054, respectively. Genetic distances between population from Rio Grande do Sul and other populations are presented.